Use of Digital Technology in Learning Islamic History to Improve Understanding of Religion in Schools - M. Hamzah Alfiansyah; Adi Rosadi (Penerbit Presisi Pustaka, 2026)
The integration of digital technology in Islamic education, particularly for teaching complex historical subjects, remains a significant challenge due to inadequate teacher preparation and a focus on technological mechanics over spiritual understanding. This study aims to analyze the implementation of digital projectors in learning Islamic history and its impact on enhancing students' religious comprehension. Using a qualitative narrative approach, this field research collected data through in-depth interviews with two teachers and participatory observation at Madrasah Diniyah Attabi'iyah Awaliyah. The findings indicate that digital visualization significantly increases student engagement and conceptual understanding of Islamic historical events. However, the study also identifies critical challenges, including unstable internet connectivity, electricity dependency, and the potential for technology to overshadow the teacher's central pedagogical role. The conclusion emphasizes that successful technology integration requires a balanced, blended learning approach that positions digital tools as complements to, rather than replacements for, conventional teaching methods. The theoretical implication reinforces the Technological Pedagogical Content Knowledge framework with a spiritual dimension, while the practical implication underscores the need for teacher training that synergizes technological competence and spiritual pedagogy, alongside the development of religious-based digital content.